Diabète de type 1 et sport de haut niveau/professionnel - Radermecker, R. P.; Systermans, S.; Bekka, S.; Kaux, J. F. (Science & Sports, 2019)
Objective: Sports practice in people with type 1 diabetes generates increased metabolic stress. The present article aims at describing various principles that are essential to achieve a high levels of athletic performance in type 1 diabetics, such as: various regimes of insulin delivery and their corresponding regulation, different methods for measuring blood glucose, co-medication, type of exercise, timing of exercise, nutrition, and relatives involvement. Material and method: PubMed search using the following keywords, Type 1 diabetes, Sport, Athlete, Insulin, Glycaemia. Results: Sports performances at higher level is possible despite the additional constraints imposed by type 1 diabetes. The athlete can however only reach these performances if he and hisrelatives are actively taking various important parameters under careful consideration. Each type 1 diabetic athlete is unique and evolves individually, making it difficult to provide a single set of recommendations for all type 1 diabetics who want to practice sport. In conclusion, it is only through a series of tests taking many endogenous and exogenous parameters into account, some of which are hardly controllable, that a glycemic balance can be attained and high level sports performances can be achieved.